PROPORTIONAL THINKING MECHANISM: EFFECTIVENESS OF DUAL-PROCESSING METHOD IN OVERCOMING NUMERATION OBSTACLES IN CHEMISTRY LEARNING FOR 3T STUDENTS - Damayanti, Yosephine Debbie; Putri, Rinda Angghita (International Journal of Active Learning, 2025)
This study aims to examine the effectiveness of the dual-processing method in improving the proportional thinking skills of 3T students in chemistry learning, especially in dealing with numeracy barriers. The dual-processing method refers to a cognitive theory that combines intuitive thinking (System 1) and analytical thinking (System 2) to improve students' conceptual understanding and numeracy skills. This study used a quantitative and qualitative approach with a pre-test and post-test experimental design and observation of student participation during the learning process. The results showed that after the dual-processing method intervention, there was a significant increase in students' numeracy skills, with an average post-test score increasing by 33.5 points compared to the pre-test. In addition, this method also helps reduce academic anxiety and increase students' confidence in solving numeracy problems. Classroom observations showed that students were more active in discussions and more reflective in solving chemistry problems than before the intervention. The dual-processing method has been proven effective in improving 3T students' numeracy understanding and overcoming proportional thinking barriers in chemistry learning. Therefore, the integration of this method into the higher education curriculum is recommended to improve students' critical and analytical thinking skills in numeracy-based disciplines.